Hunter-Schreger Band configuration in human molars reveals more decussation in the lateral enamel of 'functional' cusps than 'guiding' cusps. (October 2022) - Yang, Deming; Bharatiya, Maya; Grine, Frederick E.
Abstract: Objectives: Enamel prism decussation, which manifests as Hunter-Schreger Bands (HSB), is considered a mechanism to mitigate crack propagation. During the chewing cycle, the 'functional' cusps that are involved in Phase II crushing and grinding experience more complex patterns of stress than do those that 'guide' the molars into occlusion (Phase I). This study examines HSB configuration in the lateral enamel of human molars to identify potential differences between these cusps as predicted from their functional distinctions. Design: Measurements were recorded from scanning electron micrographs of sections through the mesial cusps of unworn permanent molars. For each section, HSB packing density and the relative thickness of decussated enamel were quantified in the cuspal and middle segments of lateral enamel over the guiding and functional cusps. Results: No clear trend from first to third molars in HSB configuration was found in either jaw. In maxillary molars, the functional cusp displays higher HSB packing density in the cuspal and middle segments, and relatively thicker decussated enamel in the cuspal segment than does the guiding cusp. In mandibular molars, the functional cusp displays higher HSB packing density in the middle segment than does the guiding cusp, but no difference in relative thickness was found between them. Enamel of mandibular molars shows weaker decussation than maxillary molars. Conclusions: The results suggest that guiding cusps are intrinsically more susceptible to crack propagation than functional cusps in human permanent molars. Structural factors such as enamel decussation should be considered when interpreting enamel chipping patterns in dietary contexts. Highlights: Functional cusps display stronger enamel decussation than guiding cusps of the same tooth. Maxillary molars display stronger enamel decussation than mandibular molars. Enamel decussation patterns can explain observed dental chipping frequencies.